Perancangan Conveyor Untuk Sorting Bibit Ikan Nila Berdasarkan Ukuran Panjang Menggunakan Sensor Pada Kolam Tambak Ikan UMKM Batriard Fish Farm Di Kabupaten Bandung - setrayudha, wulung (LPPM-ITEBA, 2025)
Indonesia has abundant fishery resources. In 2020, West Java Province produced 250,543 tons of fish. One of the fishery-based SMEs in Bandung Regency is Batriard Fish Farm. Based on interviews, this SME requires an automated system to count and sort tilapia fry by size. The fry to be sorted totals 500,000 fish, with a length range of 30–50 mm and a weight range of 7–20 grams. The system must operate with a 1,300 VA power supply, complete sorting in under 16 hours (faster than manual sorting), and keep the fish alive.Using the VDI 2222 method, the design process consists of four stages: planning, conceptualization, designing, and finalization. The planning stage involves gathering key specifications from interviews. Next, three conceptual variants were developed and evaluated, with the highest-scoring concept selected for further design. The chosen conveyor-based sorting system can process live tilapia fry with a response time of 87 milliseconds (from input to sorting), consumes 68 W of power, and applies a 0.1 N force via the sorting arm to ensure the fry remain unharmed.